2015
DOI: 10.1021/acs.jpca.5b00069
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Atomic Polarizabilities of Amino Acids and their Hydrogen-Bonded Aggregates

Abstract: With the purpose of rational design of optical materials, distributed atomic polarizabilities of amino acid molecules and their hydrogen-bonded aggregates are calculated in order to identify the most efficient functional groups, able to buildup larger electric susceptibilities in crystals.Moreover, we carefully analyze how the atomic polarizabilities depend on the one-electron basis set or the many-electron Hamiltonian, including both wave function and density functional theory methods. This is useful for sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 68 publications
2
65
0
Order By: Relevance
“…Quantumm agnets are appealing materials, consisting of spin centers coupledt hrough exchange interactions. [248] Quantumc rystallographic approaches also enable the characterization of non-equilibrium phenomenai nm olecular crystals, due to photo-excitation or X-ray probe pulses. Superconducting quantum interference or muon spin spectroscopy are methods to measurem agnetic susceptibility,s patial ordering and spin dynamics, and thereafter derive simplem odels of exchange.…”
Section: Quantumc Rystallography and Materials Sciencementioning
confidence: 99%
“…Quantumm agnets are appealing materials, consisting of spin centers coupledt hrough exchange interactions. [248] Quantumc rystallographic approaches also enable the characterization of non-equilibrium phenomenai nm olecular crystals, due to photo-excitation or X-ray probe pulses. Superconducting quantum interference or muon spin spectroscopy are methods to measurem agnetic susceptibility,s patial ordering and spin dynamics, and thereafter derive simplem odels of exchange.…”
Section: Quantumc Rystallography and Materials Sciencementioning
confidence: 99%
“…A general trend in the analysis of organic molecules is that atomic polarizabilities are much larger in the bonding directions and especially elongated along bonds with large electronegativity differences . Furthermore, C α ‐atoms in amino acids and aromatic rings have been shown to have great importance for molecular polarizabilities, with the latter also being highly anisotropic, and the transferability between amino acids showed promise for tabulating functional group polarizabilities . An important addition in molecular aggregates is the importance of hydrogen bonds, which have a two‐fold influence on the properties by polarizing the hydrogen bonded functional groups, leading to larger anisotropy and an increase in polarizability by 10–20 %, and by orienting the molecules in a specific bonding pattern, which often leads to enhanced properties along specific directions (Figure ) .…”
Section: Materials Classesmentioning
confidence: 99%
“…[110,112] Furthermore, C a -atoms in amino acids and aromatic rings have been shown to have great importance for molecular polarizabilities, with the latter also being highly anisotropic, and the transferabilityb etween amino acids showed promise for tabulating functional group polarizabilities. [113] An importanta ddition in molecular aggregates is the importanceo fh ydrogen bonds, which have at wofold influence on the properties by polarizing the hydrogen bondedf unctional groups, leadingt ol arger anisotropy and an increasei np olarizability by 10-20 %, and by orienting the molecules in as pecific bondingp attern, which often leads to enhanced properties alongs pecific directions (Figure 9). [112,114] The method hasa lso been appliedt om etal-organic frameworks, where it was shown that the largest contribution to the refractive indices arose from the coordination of the metal atom, resulting in larger refractive indices along directions of coordination bonds, whereas the type of metal atom had only negligible influence on the properties.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Thus, although there are some theoretical studies regarding the variations of infrared intensities for the XH stretching modes of simple dimers, along with investigations dealing with the perturbation caused by hydrogen bonds in molecular polarizabilities of amino acids and the cooperative effects of these interactions on water clusters, the study of charge redistributions during the formation of more complicated dimers is still scarce. For example, bidentate dimers (HCOOH…HCOOH, FCOOH…FCOOH, among others), which can be bonded by two HBs between hydroxyl and carbonyl groups (O…H), have not yet been subjected to infrared intensity variation investigations via the CCFDF/QTAIM model, although they were analyzed by the equilibrium charges charge flux (ECCF) model, which does not include terms to deal explicitly with the variations in atomic polarizabilities …”
Section: Introductionmentioning
confidence: 99%